The impact of private capital flows on economic growth in the MENA region - Ben-Salha, Ousama; Zmami, Mourad (Economics and Business Review, 2020)
The aim of the article is to conduct an empirical analysis of the impact of aggregate and disaggregate private capital flows on economic growth in eleven MENA countries between 1980 and 2018. Unlike prior empirical studies, the fixed effect panel quantile approach developed by Canay (2011) is implemented. Findings suggest that there is a significant difference in the effects of private capital flows on economic growth across lower and higher quantiles. More specifically, the effects of total private capital flows, foreign direct investment flows, portfolio flows and debt flows are positive and statistically significant only for low and medium quantiles, indicating that the enhancing impact of private capital flows in terms of economic growth is only confirmed in countries with relatively low and medium growth rates. Moreover, debt flows affect economic growth in countries recording high growth rates, stressing the importance of financial development in routing those flows into the most productive projects in the economy.